Generally Applicable Transformation Protocols for Fluorescent Nanodiamond Internalization into Cells - Simon R. Hemelaar (Nature Portfolio, 2017)
Abstract Fluorescent nanodiamonds (FNDs) are promising nanoprobes, owing to their stable and magnetosensitive fluorescence. Therefore they can probe properties as magnetic resonances, pressure, temperature or strain. The unprecedented sensitivity of diamond defects can detect the faint magnetic resonance of a single electron or even a few nuclear spins. However, these sensitivities are only achieved if the diamond probe is close to the molecules that need to be detected. In order to utilize its full potential for biological applications, the diamond particle has to enter the cell. Some model systems, like HeLa cells, readily ingest particles. However, most cells do not show this behavior. In this article we show for the first time generally applicable methods, which are able to transport fluorescent nanodiamonds into cells with a thick cell wall. Yeast cells, in particular Saccharomyces cerevisiae, are a favored model organism to study intracellular processes including aging on a cellular level. In order to introduce FNDs in these cells, we evaluated electrical transformation and conditions of chemical permeabilization for uptake efficiency and viability. 5% DMSO (dimethyl sulfoxide) in combination with optimized chemical transformation mix leads to high uptake efficiency in combination with low impact on cell biology. We have evaluated all steps in the procedure.